Real-time damage detection for flexible structures using transient vibrational response. - De Abreu, Robert. (University of Ottawa (Canada), 1999)
Flexible structures are often composed of a number of flexible parts connected together by rivets or bolts. Over time, the connections can become loose, creating a danger of structural integrity failure. During system operation, real-time monitoring to detect structural damage is required. In this thesis, a new non-destructive testing method to detect damage in structural connections using piezoelectric actuating/sensing devices is proposed. A thin beam with one end fixed and the other subjected to a variety of boundary conditions is used to investigate the feasibility of this method. The method involves first flexurally exciting the beam and measuring its resulting transient vibrational response using piezoelectric devices, and then determining any change in its one variable boundary condition by comparing the measured response to that of a fixed-fixed (or secure) condition. The size of the difference in the responses indicates the extent of the boundary change. These differences are quantified by the use of damage indices. The proposed transient response approach uses information that cannot be obtained using current steady-state harmonic-based methods. Results of experiments and damage index analyses show that several of the differences in the transient responses of the beam are significantly and monotonically dependent on the level of damage of the connections.
Keywords: Engineering, Mechanical.